Persuasive Diction in Presidential Discourse: A Critical Discourse Analysis of Prabowo Subianto’s National Speech - Sari, Lusi Komala; Apakama, Lucy Mgbengasha (Konstruksi Sosial : Jurnal Penelitian Ilmu Sosial, 2025)
This study analyzes the use of persuasive diction in President Prabowo Subianto’s state address during the post–2024 Presidential Election transition period in Indonesia. The study aims to fill a gap in research on lexical strategies in formal political discourse in Indonesia. Employing a qualitative approach through Critical Discourse Analysis (CDA), thematic analysis was conducted on the speech transcript to uncover linguistic mechanisms that construct political legitimacy, leadership identity, and national narratives. The analysis focuses on patterns of lexical choice, including evaluative terms, collective references, and the construction of future-oriented visions. The findings identify four main categories of persuasive diction: nationalistic, moral-evaluative, futuristic-visionary, and egalitarian diction. These categories operate complementarily to enhance the persuasive power of the speech and reinforce leadership legitimacy during the political transition period. This study demonstrates that lexical choices in state addresses are not neutral but function as systematic ideological strategies. The findings contribute to political discourse studies in Indonesia and Southeast Asia and are relevant to the development of critical media literacy, political rhetoric analysis, and the understanding of leadership construction in contemporary democratic contexts.